Post-acute COVID-19 Syndrome: Brain Fog Phenotype, Patient-Centric Understanding, and Biopsychosocial-Oriented Treatment - Bender, Heidi A; Williams, Natalie A; Burnfield, Judith M; Constantinidou, Fofi; Bossuyt, Fransiska M; Bergquist, Thomas; Bogdanova, Yelena; Cohen, Evan; Raber, Jacob; Lokai, Andrew D; Sacks-Zimmerman, Amanda (Archives of physical medicine and rehabilitation, 2025)
Post-acute COVID-19 syndrome (PACS), a term used to describe ongoing symptoms after SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2) (COVID-19) infection, includes prominent neuropsychological sequela, such as a subjective sense of brain fog. Brain fog can be persistent and interfere with quality of life and daily functioning across multiple domains. Rehabilitation professionals can comprehensively address PACS-related brain fog through a biopsychosocial framework of chronic illness. Through emphasizing a patient-centric perspective, rehabilitation practitioners can understand lifestyle protective factors, as well as the reciprocal relationships between emotional processing and behaviors that potentially maintain symptomology manifesting as brain fog. However, current practice models do not fully address the biopsychosocial components for adults suffering from PACS-related brain fog. To address gaps in the literature, we present a biopsychosocial framework for PACS-related brain fog and provide treatment strategies based on evidence from current literature of neuropsychiatric sequela of mild traumatic brain injury. These recommendations will provide practice guidance to rehabilitation professionals in (1) identifying common protective factors that can be optimized in the context of persistent PACS-related brain fog and (2) addressing these symptoms via integrative interventions, considering the biopsychosocial presentation of brain fog.